Partial plant models in formal verification of industrial automation discrete systems - Machado, José Mendes (2011)
The use of a plant model for formal verification of Industrial Automation systems controllers must be used in order to improve the obtained results. However, if there are some cases where the use of a plant model makes the formal verification results more realistic and robust, there are other cases where this does not always happen. The discussion presented in this paper is related with the need of using a Plant Model considering, not all of the Plant Model, but Partial Plant models in order to facilitate formal verification tasks of Industrial Automation Discrete Event Systems.